2013
DOI: 10.1177/0003122413491964
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Immigration, Violence, and City-Level Immigrant Political Opportunities

Abstract: Using a multilevel comparative framework, we propose that politically receptive city contexts facilitate the viability of marginalized neighborhoods. To illustrate this proposition, we examine the relationship between immigrant concentration and neighborhood violence. Drawing on political process and minority incorporation theories, we argue that favorable immigrant political opportunities will strengthen the often-found inverse relationship between immigration and crime at the neighborhood level. Unique data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
177
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(193 citation statements)
references
References 85 publications
14
177
2
Order By: Relevance
“…Perhaps immigration has played a role in buffering killings? Certainly in the United States, there is evidence supporting the immigrant revitalization hypotheses [28]. Second, immigrants help fortify social organization.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps immigration has played a role in buffering killings? Certainly in the United States, there is evidence supporting the immigrant revitalization hypotheses [28]. Second, immigrants help fortify social organization.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ramey (2013) found that the relationship between neighborhood-level immigrant composition (and growth) and violence depends on the racial/ethnic composition of the neighborhood and the destination type of the larger MSA in which the neighborhood is located. Lyons et al (2013) observes that the protective, revitalizing effects of immigrant concentration on neighborhood-level violence are amplified in metropolitan areas with receptive political climates. Likewise, in their seminal study, Peterson and Krivo (2010) illustrate that immigrant concentration at the neighborhood-level is linked to lower levels of violence and property crime, regardless of the immigrant composition of surrounding census tracts.…”
Section: Advantages Of Immigrant Spatial Concentrationmentioning
confidence: 99%
“…In turn, scholarly interest in immigration and crime has been rekindled as social scientists revisit these relationships for the newest waves of immigration. As a result, there is now a sizable and growing body of research examining aggregate-level relationships between immigration and crime (Desmond and Kubrin, 2009;Feldmeyer, 2009;Feldmeyer and Steffensmeier, 2009;Harris and Feldmeyer, 2013;Lyons et al, 2013;Martinez, 2002;Martinez et al, 2008Martinez et al, , 2010Nielsen et al, 2005;Ousey and Kubrin, 2009;Ramey, 2013;Reid et al, 2005;Sampson et al, 2005;Barranco, 2010a, 2010b;Stowell, 2007;Wadsworth, 2010). The general conclusion from these studies is that the relative size of the immigration population has either neutral effects or is linked to lower rates of crime and violence in U.S. locales after controlling for other macro-structural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…9 For example, children and families possessing less cultural and educational capital may feel alienated because they feel that only well-educated people use libraries, they do not know how to use a library, or they "feel stupid" asking questions. 10 Additionally, many immigrants affected by poverty-another oft-marginalized group 11 -come from cultures where socializing in public places is the norm and therefore may feel uncomfortable with the enforced silence and language barriers at public libraries in the United States. 12 Schools serving high-poverty areas, meanwhile, are also not equipped to provide their students with ideal library services, since they may have fewer resources than schools serving more affluent communities.…”
Section: Libraries Access To Books and Social Exclusionmentioning
confidence: 99%